From Complaints to Opportunities: Analyzing Grievance Trends and Responsiveness in the 4Ps - Kris Ann M. Melad (Philippine Institute for Development Studies (PIDS), 2023)
The 4Ps grievance redress system (GRS) is designed to facilitate due process in resolving the concerns and complaints of beneficiary households, program stakeholders, and the general public about the program. As with other social programs globally, the 4Ps GRS serves as a social accountability measure in response to risks of error, fraud, corruption, and leakages due to the intensive requirements and complexity of its operations. This study investigates the 4Ps GRS by analyzing grievance case data from 2010 to 2022. Key patterns and challenges emerged, with a notable increase in grievance volume following procedural guideline upgrades and calamitous events, while cases declined due to malfunctioning Management Information Systems (MIS). Payment-related issues topped grievances in terms of volume, reflecting challenges in cash transfer distribution as expected since the payment of grants is a key feature of a conditional cash transfer. In-person modes dominated grievance filing, emphasizing the importance of direct interaction and capacity building of staff to manage grievances effectively. Grievance resolution rates were generally high, but a decline in 2021-2022 highlighted a need for review of procedures. Regression analysis indicated factors influencing timely resolution, including mode of submission and regional disparities. Interviews from previous studies revealed limited beneficiary awareness, cases of delayed resolutions, and a need for better access to case updates. Recommendations include strengthening data management, improving staff capabilities, promoting beneficiary awareness, and implementing regular evaluation and monitoring. These findings underscore the necessity of targeted approaches for grievance resolution in the 4Ps program.
Keywords: 330; Grievance Redress; 4Ps; Cash Transfer; resolution timeline; survival analysis